2010
DOI: 10.1111/j.1365-2702.2010.03194.x
|View full text |Cite
|
Sign up to set email alerts
|

Hand dermatitis among paediatric nurses

Abstract: The proper preventive programmes should be implemented for those nursing staff working in high-risk units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 23 publications
1
16
0
2
Order By: Relevance
“…This confirms what has been previously reported in the literature [16] [17] [18] [19] , as well as showing both results for the first time in a single population of healthcare workers. In Cleveland, Ohio, where our study took place, the year is typically divided into 6 months of cold and 6 months of warm weather.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This confirms what has been previously reported in the literature [16] [17] [18] [19] , as well as showing both results for the first time in a single population of healthcare workers. In Cleveland, Ohio, where our study took place, the year is typically divided into 6 months of cold and 6 months of warm weather.…”
Section: Discussionsupporting
confidence: 92%
“…Low temperature and low relative and absolute humidity (such as during the winter season) tended to be risk factors for and contributed to the development of IHD [16] . Higher levels of handwashing were also found to be associated with the development of hand dermatitis [1719] . Overall, it is not evident whether endogenous or exogenous factors make a stronger contribution to the development of IHD, and for that reason, it would be helpful to evaluate all these factors in the same population.…”
Section: Introductionmentioning
confidence: 99%
“…6 The prevalence of hand eczema among hospital workers in countries other than India ranges from 6% to 80%. [7][8][9][10][11][12][13][14][15][16][17][18] However, most studies on hand eczema have been based on self-reported surveys, and have utilized varied outcome measures, and almost no epidemiological data on hand eczema among healthcare workers exist in India.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have focused on gaining insights into the prevalence of hand eczema among healthcare professionals. However, the estimates of the prevalence of this condition vary across studies . Importantly, there are very few studies on the prevalence of hand eczema in the Netherlands.…”
mentioning
confidence: 99%